Tinjauan Audit Syariah Terhadap Transaksi Digital E-Ticketing pada Entitas Syariah - Lilisyam Mulyaningsi; Fitra Naswalia; Andi Nayla Salsabila; Jaya Angriawan; Masyhuri Masyhuri (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze the compliance of digital e-ticketing transactions in Islamic entities with Sharia audit principles. The rapid advancement of information technology has encouraged the adoption of digital services, including e-ticketing systems that offer convenience, efficiency, accuracy, and speed in transaction processes. However, the implementation of such systems requires proper supervision to ensure that all transaction mechanisms comply with Islamic principles and ethical standards. This research employs a qualitative method using a literature review approach by examining relevant journals, books, regulations, and fatwas related to digital transactions and Sharia auditing. The findings reveal that digital e-ticketing transactions can be considered Sharia-compliant when they fulfill the requirements of clear contractual agreements (akad), transparent information disclosure, fair pricing mechanisms, and the absence of prohibited elements such as riba (usury), gharar (uncertainty), and maysir (gambling). Furthermore, Sharia auditing plays a crucial role in identifying potential non-compliance issues, evaluating the implementation of Islamic principles, and providing recommendations for continuous improvement. Effective and sustainable Sharia audits contribute to strengthening Sharia compliance, enhancing user trust, maintaining the integrity of digital transactions, and supporting the development of technology-based services that align with Islamic values and the objectives of maqashid al-shariah in modern financial and service environments.